Investigations on The Mechanism of Artificial Photosynthesis of Ca-Pc-PDI and Dendrimer Molecule by DFT Calculations - Gunawan, Rahmat; Hammamiyah, Ulinnuha; Fadillah, Fahmi; Saleh, Chairul; Sitorus, Saibun (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2018)
Artificial photosynthesis modelling of Ca-Pc-PDI complex Ca Phthalocyanine Perylenediimide), and dendrimer molecule using Density of Functional Theory (DFT) Method has been studied to showed the energy efficiency of these compounds in terms of electron transfer in photosynthesis. The Analysis of Ca-Pc-PDI and dendrimer compound and also chlorophyl has been done in all computations using the GAMESS-US software. The computations result in this research showed that the large wavelength complex compounds of Ca-Pc-PDI obtained was 138.3299 nm and energy efficiency obtained was 0.89 eV. The data analysis states that the absorption of harvest light energy of complex compounds Ca-Pc-PDI lies in the far UV spectrum. The other side, the polyphenylene dendrimer structure molecular orbital analyses it was found that the dendrimer was capable of electron transfers as indicated by the existence of HOMO and LUMO and result comparisons with chlorophyll. UV wavelengths of the polyethylene dendrimer and chlorophyll, respectively, suggesting that the polyphenylene dendrimer is capable of substituting chlorophyll in artificial photosyntheses. We can states from the result that these compound ability to be applied in the modeling of artificial photosynthesis as a material of energy absorption that mimics the workings of chlorophyll in terms of electron transfer in natural photosynthesis process. Keywords: Artificial photosynthesis modelling, Ca-Phthalocyanine-Perylenediimide complex, and dendrimer molecule